1997
DOI: 10.1007/s004410050955
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-protein toxicity and oxidative stress in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by loss of memory and progressive decline of cognitive abilities. Although the pathogenesis of this disease is not known and is still under intensive investigation, there are several hypotheses which address certain aspects of the disease. This review focuses on the oxidative-stress hypothesis of AD and on novel antioxidative approaches to an effective neuroprotection for the prevention and therapy of this neurodegenerative disorder. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
136
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 125 publications
(105 reference statements)
3
136
0
4
Order By: Relevance
“…A promotes neurite outgrowth, generates reactive oxygen intermediates, induces cytotoxic cellular oxidative stress, and microglial activation (Koo et al, 1993;Behl, 1997;Sasaki et al, 1997). Although the mechanism by which A peptides cause enhanced expression of proinflammatory cytokines from microglia, is not fully understood there is evidence that A may interact with cell-surface receptors, including receptors for advanced glycosylated endproducts (RAGE) and scavenger receptors (El Khoury et al, 1996;Yan et al, 1996).…”
Section: Molecules Involved In Microglial Activation and Signal Transmentioning
confidence: 99%
“…A promotes neurite outgrowth, generates reactive oxygen intermediates, induces cytotoxic cellular oxidative stress, and microglial activation (Koo et al, 1993;Behl, 1997;Sasaki et al, 1997). Although the mechanism by which A peptides cause enhanced expression of proinflammatory cytokines from microglia, is not fully understood there is evidence that A may interact with cell-surface receptors, including receptors for advanced glycosylated endproducts (RAGE) and scavenger receptors (El Khoury et al, 1996;Yan et al, 1996).…”
Section: Molecules Involved In Microglial Activation and Signal Transmentioning
confidence: 99%
“…The molecular mechanisms by which A␤ contributes to oxidative damage remain unclear (11)(12)(13)(14)(15)(16)(17)(18)(19). Understanding these mechanisms, however, is critical for developing effective methods to manage the disease.…”
mentioning
confidence: 99%
“…Most studies examining A␤ toxicity in cell culture have used assays of neuronal viability, such as the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay, which assesses cellular mitochondrial function (Liu et al, 1997). By using this approach and other techniques, A␤ has been shown to be neurotoxic in cell culture (Yankner, 1996;Behl, 1997). Several studies have implicated free radicals (Behl, 1997) or calcium (Mattson et al, 1992) in the neurotoxic mechanism.…”
mentioning
confidence: 99%
“…By using this approach and other techniques, A␤ has been shown to be neurotoxic in cell culture (Yankner, 1996;Behl, 1997). Several studies have implicated free radicals (Behl, 1997) or calcium (Mattson et al, 1992) in the neurotoxic mechanism. A number of studies have shown that A␤ toxicity is dependent on the degree of aggregation of the peptide (Pike et al, 1991;Lorenzo and Yankner, 1994).…”
mentioning
confidence: 99%